PERBEDAAN INFORMASI ANATOMI CITRA MRI CERVICAL PADA KASUS HERNIA NUCLEUS PULPOPUS (HNP) DENGAN SEKUEN T2W FAST SPIN ECHO (FSE) ANTARA PENGGUNAAN FLOW COMPENSATION DAN TANPA FLOW COMPENSATION - Nidaa Azmii Susdiningtyas; Farrah Hendara Ningrum; Nanang Sulaksono; Sudiyono (Perhimpunan Radiografer Indonesia (PARI), 2019)
Background : Flow compensation is one technique that can reduce artifacts due to the flow of cerebrospinal fluid in MRI examination of the cervical in cases of Hernia Nucleus Pulposus specifically in T2 Weighted Fast Spin Echo (FSE) sequence images. Method : This research is quantitative study with an experimental approach. This study using 10 pasient at Cempaka Putih Hospital in Jakarta. Wilcoxon test to determine the level of cervical MRI anatomical information distribution in the case of HNP between using flow compensation and without flow compensation, mean rank value to get the better image information. Result : From the results of statistical tests, it is known that there are differences in Cervical MRI image information in the HNP case with the T2W FSE between the use of flow compensation and without flow compensation as indicated by the p-value 0.000 (p-value ≤ 0.05), this difference is due to flow compensation which can suppress flow artifacts on objects resulting in a better picture. The mean rank value in the overall anatomy of the MRI Cervical MRI image shows a better value using flow compensation with the highest value in the anatomy of the intervertebral disc, CSF, and spinal cord, 5.00 in axial view. Whereas the sagittal view in the anatomy of the vertebral corpus and spinal cord show the same value between using flow compensation and without flow compensation. Conclusion : There are differences in overall anatomical image information of MRI Cervical using flow compensation and without Flow compensation except corpus vertebralis and spinal cord in sagital view.